2023
DOI: 10.3390/ani13050918
|View full text |Cite
|
Sign up to set email alerts
|

An Explorative Study of the Causal Pathogenesis of Green Liver Discoloration in Organically Reared Female Bronze Turkeys (Meleagris gallopavo) Considering the Infectious Risk Factors

Abstract: A recent study revealed that organically raised Bronze turkeys showed a high prevalence of green liver discoloration. This alteration is commonly associated with the Turkey Osteomyelitis Complex and potentially caused by opportunistic bacteria. Therefore, 360 organically fattened Bronze turkeys were examined post-mortem throughout two fattening trials with two examinations each to determine possible infectious risk factors and reduce disease prevalence. Clinical and pathoanatomical examinations were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The findings of the performed blood and liver analyses in this study give insight into the formal pathogenesis of green liver discoloration, suggesting a flock-specific subacute etiology at the age of 70 to 75 days and an individual, more acute etiology at the age of 120 to 127 days of fattening. This complements the findings concerning the causal pathogenesis of GL by Cuta et al [12] who presented a correlation of GL with the immunosuppressive hemorrhagic enteritis virus during the early fattening stage and joint or bone lesions or both in the late fattening stage. These results support the previously made assumption that a weakened immune system plays a bigger role in the development of GL than a single pathogen [11].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The findings of the performed blood and liver analyses in this study give insight into the formal pathogenesis of green liver discoloration, suggesting a flock-specific subacute etiology at the age of 70 to 75 days and an individual, more acute etiology at the age of 120 to 127 days of fattening. This complements the findings concerning the causal pathogenesis of GL by Cuta et al [12] who presented a correlation of GL with the immunosuppressive hemorrhagic enteritis virus during the early fattening stage and joint or bone lesions or both in the late fattening stage. These results support the previously made assumption that a weakened immune system plays a bigger role in the development of GL than a single pathogen [11].…”
Section: Discussionsupporting
confidence: 88%
“…On the contrary, at days 70 to 75 of fattening, a more chronic inflammation process seems to take place in flocks affected by GL (high lymphocyte counts in individuals, high leucocyte numbers in affected flocks, and low ALB on both the flock and the individual level). These results complement the findings by Cuta et al [12] who found reduced body weights and a higher prevalence of inflammatory reaction within the livers of turkey hens with GL compared to turkeys without liver discoloration during both stages of the fattening period. A correlation was shown between GL at 70 to 75 days of fattening and the detection of hemorrhagic enteritis virus as an immunosuppressive agent as well as GL at 120 to 127 days of fattening and bone or joint lesions or both, suggesting 2 different pathogeneses of the disease [12].…”
Section: Clinical Chemistry Analysessupporting
confidence: 90%
See 2 more Smart Citations